Measuring and building resilience in undergraduate nursing students in South Africa - Maloney, Caroline Lilian (My University, 2018)
Background The health care environment is a challenging place for all health care professionals. Nurses with high levels of resilience are known to cope better with the stressors of a constantly changing health care environment. Resilient nursing students are also more likely to complete their courses and remain in the nursing profession once qualified. Methodology Nursing students following the Baccalaureate Degree in Nursing at two educational institutions in South Africa formed the sample for this mixed methodology study. In the quantitative phase self-measurement of resilience levels was done using the ConnorDavidson Resilience Scale. In the qualitative phase of the study, volunteers from the student group were interviewed using a semi-structured questionnaire, to determine how best to improve resilience levels in student nurses. The quantitative and qualitative data were integrated to create a rich description of resilience levels of student nurses in South Africa, with ideas of how to improve their resilience levels. Results The total resilience scores for each institution were found to be very similar. The more senior students had higher scores than their first and second year counterparts and women had higher scores than men. Three main categories with intrinsic, extrinsic and combination factors were identified. The integrated findings suggest that most resilience- building factors can be developed and improved upon. Conclusion Creating resilient, and positive nurses should be a mandate of all nursing education institutions who should assist nursing students to build and sustain resilience levels.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of requirements for the degree of Master of Science in Nursing.